A Tale of Convergence? Discrimination based on Sexual Orientation in Regional Human Rights Bodies and the Human Rights Committee. Issue 3 (3rd July 2017) - Abrusci, Elena
ABSTRACT: The International Covenant on Civil and Political Rights (ICCPR) and the regional human rights conventions do not explicitly prohibit discrimination based on sexual orientation, or provide the right to marry and have a family for same-sex couples, thus leaving an open margin of interpretation to their judicial and quasi-judicial enforcement bodies. However, regional courts and the Human Rights Committee (HRC) jurisprudence seems to have followed a path of convergence rather than fragmentation. This article will analyse the case-law of the regional judicial bodies and of the HRC on the matter through the lens of the prohibition of discrimination, assessing how such convergence has been reached and evaluating its nature. The analysis will reveal that beneath a seeming trend of convergence in the case outcomes, there are signs of a strong point of divergence and many threats of future fragmentation. In particular, there is a deep contrast between the European and the Inter-American Court of Human Rights in terms of prohibited discrimination based on sexual orientation. Moreover, the convergence reached among regional human rights bodies and the HRC hides vague and highly debated concepts and definitions on sensitive topics like marriage and adoption.